Gas exchange responses to constant work rate exercise in chronic cardiac failure. Issue 2 (August 1994) - Riley, M; Pórszász, J; Stanford, C F; Nicholls, D P
Abstract : OBJECTIVE–To examine the time course of changes in minute oxygen consumption and other gas exchange variables and heart rate during constant work rate exercise in patients with chronic cardiac failure. DESIGN–Treadmill exercise with on line measurement of gas exchange and a target duration of 10 minutes. SUBJECTS–Seven men in New York Heart Association class II, six in class III, and seven controls. MAIN OUTCOME MEASURES–Gas exchange variables and heart rate were averaged for the final two minutes of exercise. Time constants were calculated for the increase in all variables. RESULTS–Consumption of oxygen at the end of exercise (VO2) was similar in class II patients (mean (95% confidence interval (95% CI) 14.9 (13.6 to 16.1) ml kg-1 min-1), class III patients (13.2 (11.2 to 15.1) ml kg-1 min-1), and controls (13.3 (12.5 to 14.2) ml kg-1 min-1). The patients reached this VO2 more slowly with longer exponential time constants of 0.82 (0.59 to 1.04) min in class II and 1.19 (0.86 to 1.51) min in class III, than the 0.49 (0.35 to 0.64) min in the controls. Time constants of other gas exchange variables and heart rate were also longer in patients. By analysis of covariance, peak VO2 accounted for the between group difference in the time constant for VO2, suggesting that circulatory factors may be an important cause of the delayed kinetics. CONCLUSIONS–A delayed rise in VO2 in response to exercise may be responsible for subnormal values of VO2 early in exercise in patients with chronic cardiac failure.